Flex on Java - Allmon, Bernerd (Manning, 2011)
Unlike many Flex books that presume readers want to develop applications from scratch, Flex on Java is for developers in the real world-where Flex is one more technology being added to existing systems developed in Java, and where integration is the key indicator of success. Written for Java developers beginning to use Flex, Flex on Java shows how to use Flex alongside existing Java applications, and how to integrate Flex using familiar server-side technologies such as Spring, EJBs, JMS, and more. The authors, both Agile development experts, focus on Agile and test-driven development to enable readers to redesign applications that deliver more value and with zero defects. Throughout the book, readers will apply these techniques to refactoring a single application into a rich internet application using Flex and the BlazeDS framework.